Black Adam : the dark age - Tomasi, Peter (DC Comics, 2022)
"With the power of the gods stripped from him, Teth-Adam is on a quest to find both the magical word that will restore him as Black Adam and the one thing that has always kept his heart from turning completely black with rage--his deceased wife."--Publisher description.